PROPHYLACTIC MEASURES AGAINST COMMUNICABLE DISEASES W.S.R TO COVID-19: AN AYURVEDIC APPROACH (International Journal of Ayurveda and Pharma Research, 2020)
Ayurveda, the ancient treasure of medical knowledge descended to earth with two aims to serve human beings i.e Swsathasya swasthya rakshanam (Promotive and Preventive measure) and Aturasya vikara prashamanam (curative measures). Ayurveda categorized diseases into two Nija (diseases caused by endogenous factors) and Agantuja (diseases caused by exogenous factors). The term Agantuja implied in broad spectrum under which external trauma and organisms such as bacteria, virus, fungi all been incorporated. Ayurveda described communicable diseases and their causes, mode of transmission, prevention as well as cure under Janapadodhwamsa (Epidemics), Aupasargika roga (infectious diseases), Sankramika roga (Communicable diseases). In promotion of health and in prevention of diseases, Ayurveda prescribed prophylactic measures like Dinacharya (daily regimen), Ritucharya (seasonal regimen), Sadvritta (good personal and social conducts), Rasayana (Rejuvenation therapy) etc. In this article an honest attempt has been made to review systematically the prophylactic measures against communicable diseases with special reference to COVID-19 pandemic- a challenging task for medical fraternity all over the world.